RELASI SOSIAL KEAGAMAAN ANTARA MAYORITAS MUSLIM DENGAN MINORITAS NON MUSLIM NTT DI PADOLO KELURAHAN PARUGA KOTA BIMA - Syahrudin, Eky; Luthfiyah, Luthfiyah; Nasaruddin, Nasaruddin (STIT Ibnu Rusyd Tanah Grogot, 2025)
Religious social relations in Indonesia, a country marked by its religious and cultural diversity, create a unique dynamic between majority and minority groups. This study aims to explore the religious social relations between the Muslim majority and non-Muslim minorities in Padolo, Paruga Subdistrict, Bima City, West Nusa Tenggara, with a focus on aspects of tolerance, social interaction, and potential conflicts. The research employs a qualitative approach using in-depth interviews, participatory observation, and analysis of relevant documents. The findings indicate that despite differences in belief, interfaith relations in Padolo tend to be harmonious, with social solidarity acting as a balancing factor, alongside government policies that support interreligious harmony. The conclusion of this study is that social harmony in Padolo can be maintained through respect for differences, tolerance, and cooperation among groups.